Progenitor and close-in circumstellar medium of type II supernova 2020fqv from high-cadence photometry and ultra-rapid UV spectroscopy. Issue 2 (26th October 2021) - Tinyanont, Samaporn; Ridden-Harper, R; Foley, R J; Morozova, V; Kilpatrick, C D; Dimitriadis, G; DeMarchi, L; Gagliano, A; Jacobson-Galán, W V; Messick, A; Pierel, J D R; Piro, A L; et al.
ABSTRACT: We present observations of SN 2020fqv, a Virgo-cluster type II core-collapse supernova (CCSN) with a high temporal resolution light curve from the Transiting Exoplanet Survey Satellite ( TESS ) covering the time of explosion; ultraviolet (UV) spectroscopy from the Hubble Space Telescope ( HST ) starting 3.3 d post-explosion; ground-based spectroscopic observations starting 1.1 d post-explosion; along with extensive photometric observations. Massive stars have complicated mass-loss histories leading up to their death as CCSNe, creating circumstellar medium (CSM) with which the SNe interact. Observations during the first few days post-explosion can provide important information about the mass-loss rate during the late stages of stellar evolution. Model fits to the quasi-bolometric light curve of SN 2020fqv reveal 0.23 M⊙ of CSM confined within 1450 R⊙ (10 14 cm) from its progenitor star. Early spectra (<4 d post-explosion), both from HST and ground-based observatories, show emission features from high-ionization metal species from the outer, optically thin part of this CSM. We find that the CSM is consistent with an eruption caused by the injection of ∼5 × 10 46 erg into the stellar envelope ∼300 d pre-explosion, potentially from a nuclear burning instability at the onset of oxygen burning. Light-curve fitting, nebular spectroscopy, and pre-explosion HST imaging consistently point to a red supergiant (RSG) progenitor with M_ZAMS≈ 13.5\!-\!15 M_, typical for SN II progenitor stars. This finding demonstrates that a typical RSG, like the progenitor of SN 2020fqv, has a complicated mass-loss history immediately before core collapse.